Validation of a thinking abilities test for students of fourth and fifth grades of high school and freshmen at university level - Tapia M., Violeta (2010)
This paper presents the results of a research study focussing on psychometric testing aimed to evaluate quantitative and qualitative basic cognitive and superior thinking processes during reading comprehension. The cognitive and psycholinguistic domains through reading comprehension were taken in account, based on the theories the Cognitive Structure Modifiability of Reuven Feuerstein, complemented by the process theory of Margarita Sánchez; and the Textual Psycholingüistic processing of T.A Van Dijk y W. Kinysch. The selected samples were taken from male and female students of fourth and fifth grades of High School and freshmen at University level, belonging to public and private institutions. The result of the analysis showed the content validity of the instrument through expert judgment. The psychometric validation was carried out through two phases: the first one determined the difficulty index of ítems, the reliability through the ítem-test correlation and Cronbach index. After the analysis results, 13 ítems were invalidated, from which four of them, were definitively eliminated. In the second phase, the remaining nine invalidated ítems, were reevaluated after a review and improved. The new analysis showed positive results. An important aspect of the psychometric study was the Factor Analysis that permitted not only to validate the theoretical basis of the instrument, but to identify the underlying factors of the test: logic inference, categorization and analogical reasoning.